Integrative taxonomy of the species complex Haemulon steindachneri (Jordan and Gilbert, 1882) (Eupercaria; Haemulidae) with a description of a new species from the western Atlantic - Carvalho, Cintia Oliveira; Marceniuk, Alexandre Pires; Oliveira, Claudio [UNESP]; Wosiacki, Wolmar Benjamin (Elsevier B.V., 2020)
Haemulon steindachneri (Jordan and Gilbert) (Haemulidae), popularly known as cocoroca-de-boca-larga, latingrunt or latin-burro, represents a species complex found on the Atlantic western coast and on the Pacific eastern coast, condition confirmed recently by molecular phylogenies. In the present study, DNA barcoding analysis recognizes two distinct clusters; the first includes Brazil and Caribbean, and the second is composed of Pacific specimens, with genetic distance of 7.4%, differentiated by 35 base pairs. In addition to the molecular evidence, our results show morphological differences that distinguish the Atlantic lineage from that of the Pacific: anal fin, usually, with eight rays (vs. generally nine rays in Pacific); 13-15 scales below the lateral line, rarely 12 (vs. 12 scales below the lateral line, rarely 13 in Pacific), posterior margin of the maxilla robust with a slightly angled end (vs. smaller maxilla with moderately convex extremity), and presence of a spot on the preoperculum, broad and robust, with no definite shape (vs. narrow spot, with anterior extremity tuned and posterior straight, resembling a triangle in Pacific). Therefore, based on both molecular and morphological evidences, H. steindachneri is redescribed for the Pacific coast while a new species is described for the Atlantic coast.
Keywords: Marine biogeography; DNA barcode; Morphology; Western Atlantic; Eastern Pacific; Biodiversity